Pengaruh Kampanye Petisi Online Change.Org Terhadap Kesadaran Isu Paskibraka Puteri Wajib Melepas Jilbab di Masyarakat Kota Batam - Tri Putrahasan Zebua Zebua; Ageng Rara Cindoswari (LPPM Universitas Putera Batam, 2026)
Although issues related to religious freedom are often debated in Indonesia, the policy requiring female Paskibraka participants to remove their hijab has sparked a strong public reaction. This issue is in the spotlight because it touches on religious sensitivities and individual rights. The online petition campaign in Batam has covered various social issues in society. This study aims to analyze the influence of the online petition campaign on awareness of the issue of female Paskibraka being required to remove their hijab in Batam City. Data were obtained from the community through a field survey using a stratified random sampling method. Data analysis was conducted descriptively quantitatively with the help of SPSS version 26 with an analysis tool using simple linear regression. The regression results show that the change.org online petition campaign has a significant effect on awareness of the issue with a significance value of 0.001 < 0.05. The regression coefficient equation is Y = 17.88 + 0.73X, meaning that if the change.org online petition campaign increases by 1 percent, awareness of the issue of female Paskibraka being required to remove their hijab in Batam City will increase by 0.73 percent. This shows that the synergy between the dissemination of messages through online petitions allows people to understand and critically evaluate information, making the issue more acceptable to the public.